A review on sustainable mesoporous activated carbon as adsorbent for efficient removal of hazardous dyes from industrial wastewater - Kumar N.; Pandey A.; Rosy; Sharma Y.C. (My University, 2025)
Contamination of water bodies by potentially hazardous dyes has sparked widespread concern across the world. This may result in the deterioration of water quality and sources may soon start to rapidly diminish. As a result, developing effective adsorbents for eliminating these pollutants is extremely important. Mesoporous activated carbon, a relatively modern member of the carbonaceous family of adsorbents, has emerged as a promising adsorbent due to its splendid properties such as high specific surface area, large pore size and ordered pore structure, flexible surface functionalization, high porosity, and thermo-mechanical durability, etc. Many scientists have successfully studied the adsorptive properties of mesoporous-activated carbon on the removal of dyes. In this review, we have made a thorough study of mesoporous activated carbon production methods from various sources and their properties. We have also provided an insight into the adsorption mechanism of dye removal using mesoporous activated carbon and the effects of different variables on the adsorption process such as pH, adsorbent dose, temperature, initial concentration of adsorbate and modification effects on mesoporous activated carbon in attaining maximum adsorption of dyes. Furthermore, comprehensive details on adsorption isotherm and kinetic studies and the regenerative capacity of engineered mesoporous activated carbon have also been provided to get a deeper understanding of its practical applications. © 2023 Elsevier Ltd